Radiation of parotid or submandibular glands is effective for drooling in patients with parkinsonism; a randomised double-blind placebo-controlled trial. (2022) - Steenbakkers, R.J.H.M.; van Doornik, S.P.; Vissink, A.; Kerdijk, W.; van Laar, T.
Abstract: Background: Drooling is a common symptom in patients with parkinsonism, causing physical and emotional distress. It is unknown which major salivary glands are the best candidates for irradiation to reduce drooling with minimal adverse events. Therefore, this study assessed the efficacy and safety of submandibular and parotid salivary gland irradiation to reduce drooling. Methods: A prospective, randomised, double-blind, placebo-controlled trial was conducted at the University Medical Center Groningen, the Netherlands. After informed consent, 31 patients with parkinsonism and severe drooling according to the Unified Parkinson Disease Rating Scale (UPDRS) were included in this study. Exclusion criteria consisted of the use of anticholinergic drugs, the existence of salivary gland diseases, and/or an history of (pre)malignancies of the salivary glands. Patients were randomized for parotid-, submandibular- or sham irradiation (2x6 Gy with one week interval). Patients were evaluated at 1, 3, 6 and 12 months after radiation. Primary outcome measure was drooling severity according to the UPDRS. Secondary outcomes measures consisted of stimulated glandular salivary secretion rates and adverse effects. Findings: Overall 31 parkinsonian patients were included. Initially 11 patients were radiated on the parotid glands, 10 patients on the submandibular glands and 10 patients were sham-radiated. After 6 months, the sham-radiated patients were actively treated after a second randomisation. One patient in the parotid radiation group discontinued his participation after three months due to physical deterioration. Radiation of parotid or submandibular glands significantly improved the existing drooling, as compared to placebo radiation. Parotid- and submandibular radiation was equally effective, but more patients in the submandibular radiated group reported sticky saliva vs. patients treated by parotid radiation (33∙33% vs. 13∙33%). Interpretation: Major salivary gland radiation significantly improves drooling in parkinsonian patients with few adverse effects. However, parotid gland radiation is accompanied by fewer side effects and therefore is the preferred mode of radiation in this patient population.